2018
DOI: 10.1149/2.0641803jes
|View full text |Cite
|
Sign up to set email alerts
|

Connection between Phase Diagram, Structure and Ion Transport in Liquid, Aqueous Electrolyte Solutions of Lithium Chloride

Abstract: READ THESE TERMS AND CONDITIONS CAREFULLY BEFORE USING THIS WEBSITE. https://nrc-publications.canada.ca/eng/copyright Vous avez des questions? Nous pouvons vous aider. Pour communiquer directement avec un auteur, consultez la première page de la revue dans laquelle son article a été publié afin de trouver ses coordonnées. Si vous n'arrivez pas à les repérer, communiquez avec nous à

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 56 publications
6
40
0
Order By: Relevance
“…1a, we see that the results from JC-S is the one that comes closest to the measured and the literature values in the whole concentration range at 20 • C, although three ion models seem be equally well at lower concentrations. Our measured molar conductivity is also in accord with the result in a recent report [25]. At 50 • C (See Fig.…”
Section: Ionic Conductivity and Transference Numbersupporting
confidence: 92%
“…1a, we see that the results from JC-S is the one that comes closest to the measured and the literature values in the whole concentration range at 20 • C, although three ion models seem be equally well at lower concentrations. Our measured molar conductivity is also in accord with the result in a recent report [25]. At 50 • C (See Fig.…”
Section: Ionic Conductivity and Transference Numbersupporting
confidence: 92%
“…It continuously reacts with H 2 O from air. Depending on the final water content, Yim et al 36 suggested five different forms for LiCl•xH 2 O: (i) a dilute solution, (ii) a concentrated solution, (iii) molten salt hydrates, (vi) hydrous melts, and (v) the pure salt. A molar ratio of ∼4 to 7 favors the formation of a glassy state.…”
Section: Chemistry Of Materialsmentioning
confidence: 99%
“… 10 12 In recent years, Yim et al proposed a semiempirical model based on the free volume theory, which gave a good fit over the whole concentration range. 13 , 14 Different from theoretical models, the undetermined parameters in an empirical model of the electrical conductivity can be obtained by fitting the experimental data, such as the equation developed by Villullas and Gonzalez, 15 polynomial models, 16 and the Casteel–Amis equation. 17 , 18 One of the most successful empirical models is the Casteel–Amis model, which contains four parameters and can well fit the experimental data of electrolyte solutions from infinite dilution to saturation.…”
Section: Introductionmentioning
confidence: 99%